Assessment of severity and mortality of COVID‐19 with anti‐A1 and anti‐B IgM isohaemagglutinins, a reflection of the innate immune status. Issue 11 (29th July 2021) - Ozcelik, Fatih; Tanoglu, Alpaslan; Guven, Bulent Barıs; Keskin, Umran; Kaplan, Mustafa
Abstract: Aims: The relationship between the innate immune system that creates the polysaccharide antibody response and COVID‐19 is not fully understood. In this study, it was aimed to determine the predictive values of isohaemagglutinins in COVID‐19 severity/mortality. Methods: Approximately 15 440 patients diagnosed with COVID‐19 were examined, and a total of 286 patients with anti‐B and anti‐A1 IgM isohaemagglutinins test results were randomly enrolled in the study. These patients were stratified into two groups according to anti‐A1 (n: 138 blood type B or O) and anti‐B (n: 148 blood type A) IgM isohaemagglutinins. Anti‐A1 or/and anti‐B IgM, biochemical parameters, symptoms, chronic diseases, hospitalisation status, intubation status, admission to intensive care unit (ICU) and exitus status were recorded and evaluated for all patients. Results: Anti‐A1 IgM and anti‐B IgM were significantly lower in ICU patients (7.5 ± 9.9 vs 18.0 ± 20.4 and 5.5 ± 6.3 vs 19.3 ± 33.6 titres, respectively; P  < .01) and in exitus patients (3.8 ± 3.6 vs 16.7 ± 18.7 and 3.5 ± 4.7 vs 16.9 ± 29.6 titres respectively; P  < .01). In the ROC analysis performed to differentiate between exitus and discharge within groups, the sensitivity of anti‐B IgM and anti‐A1 IgM at cut‐off ≤4 was 88.9% and 79.6%, specificity 66.0% and 73.4%, and AUC 0.831 and 0.861, respectively ( P  < .01). Anti‐A1 IgM decreased the mortality risk 0.811 times per unit while anti‐B IgM decreased 0.717 times ( P  < .01). Conclusion: Anti‐B and anti‐A1 isohaemagglutinins, which are an expression of the innate immune system, can be used to predict the severity and mortality of COVID‐19 disease.